Penguatan Karakter Gotong Royong Melalui Proses Pembelajaran Pendidikan Pancasila Kelas IV SD Negeri Bugangan 02 Semarang - Purnamasari, Mita; Wuryandini, Endang; Solikhin, Riyadus; Sulianto, Joko (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to determine the strengthening of the character of mutual cooperation through the Pancasila education learning process for class IV SD Negeri Bugangan 02 Semarang. The research used a qualitative descriptive method with the research subjects being class IV teachers and class IV students at SD Negeri Butangan 02. The data collection techniques used in this research were observation, interviews and documentation.  The results of this research state that the achievement of strengthening the character of mutual cooperation which has fulfilled the 3 aspects of solidarity reached 53%, the mutual help indicator reached 47%, the respect indicator reached 73%, and the cooperation indicator reached 63%. It can be said that strengthening the character of mutual cooperation in class IV of SD Negeri Bugangan 02 Semarang is quite good.